Pelatihan Pembuatan Hand Sanitizer Berbasis Bahan Alam di Desa Lemberang, Kec. Banyumas - Desy Nawangsari; Rani Prabandari (Jurnal Pengabdian Masyarakat - PIMAS, 2022)
Piper betle L. leaf empirically has been used by the community as anti-inflamation, accelerate wound healing and antibacterial. Natural ingredients that have antibacterial activity can be found in hand sanitizer products. The use of hand sanitizer products with natural ingredients can be a more environmentally friendly alternative and reduce the risk of dry hands compared to alcohol-based hand sanitizers. Training on making hand sanitizers was carried out for community groups in Lemberang Village, Sokaraja, Banyumas, Central Java. Community service carried out in Lemberang Village began by surveying the location and characteristics of respondents, providing materials, making hand sanitizer practices, giving questionnaires and ending with closing. The event ran smoothly and based on the questionnaire given by the participants, most of them (50%) were participants aged 30-40 years, 61.76% were women. Based on the questionnaire given, the selection of natural ingredients used can be found easily (82.35%) around people's homes, and the resulting product does not cause the skin to dry out.